2023
DOI: 10.3389/fpls.2022.1099751
|View full text |Cite
|
Sign up to set email alerts
|

Increasing basal nitrogen fertilizer rate improves grain yield, quality and 2-acetyl-1-pyrroline in rice under wheat straw returning

Abstract: Straw returning plays an essential role in crop yields and the sustainable development of agriculture. However, the effects and mechanisms of nitrogen (N) fertilizer management on grain yield, quality and aroma substance 2-acetyl-1-pyrroline (2-AP) content under wheat straw returning are still unclear. In this field experiment, two japonica rice cultivars were used as materials, wheat straw non-returning (NS) and wheat straw full returning (WS) were designed coupled with two N application ratios, namely basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Our study revealed that SR application boosted accessibility of nitrogen (N), phosphorous (P), nitrates (NO 3 − ), and ammonium (NH 4 + ) within 20 cm soil depth (Figures 3-5). This is consistent with earlier reports by Zhang et al [50] and Wang et al [27]. The study revealed a significant decrease in soil phosphorus (P) availability in the SR treatment as compared to the CK treatment, specifically at depths ranging from 20 to 30 cm.…”
Section: Effect Of Rice Straw and N Fertilization On Soil Physicochem...supporting
confidence: 93%
See 2 more Smart Citations
“…Our study revealed that SR application boosted accessibility of nitrogen (N), phosphorous (P), nitrates (NO 3 − ), and ammonium (NH 4 + ) within 20 cm soil depth (Figures 3-5). This is consistent with earlier reports by Zhang et al [50] and Wang et al [27]. The study revealed a significant decrease in soil phosphorus (P) availability in the SR treatment as compared to the CK treatment, specifically at depths ranging from 20 to 30 cm.…”
Section: Effect Of Rice Straw and N Fertilization On Soil Physicochem...supporting
confidence: 93%
“…Additionally, the presence of organic matter in crop straw contributes to improved physicochemical and biological properties of the soil, resulting in increased wheat grain productivity (Figures 6 and 7). However, earlier studies have indicated that SR had no significant effect [16,25,27] or resulted in a decline in crop productivity [15,16]. This was largely ascribed to SR-induced nitrogen immobilization, resulting in decreased crop yields [16,16,27].…”
Section: Effect Of Rice Straw and N Fertilization With Topdressing On...mentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of color indices to the grain yield is mainly based on the dependence of this yield on the nitrogen content [3,4,38,107,109], which plays a key role in the grain formation and is strongly related to color parameters (see Section 4.1 and Table 2). Additionally, the nitrogen content influences the grain quality and nutritional value [144,145], i.e., these characteristics can also be related to color parameters. Vollmann et al [53] showed that R and G are moderately and negatively related to protein and oil content in soybean seeds (R 2 is about 0.45-0.65); in contrast, B is positively correlated with these characteristics (R 2 is about 0.45-0.62) (see Table 2 for details).…”
Section: For Detail)mentioning
confidence: 99%
“…China is a country with high agricultural production and is rich in agricultural straw resources. The annual output of crop straw is approximately 800 million tons, accounting for 30% of the total global output [1]. However, a complete and effective institutional mechanism for the comprehensive utilization of straw in our country has not yet been established, and the utilization efficiency of crop straw remains relatively low.…”
Section: Introductionmentioning
confidence: 99%